Direct observation of the effects of cellulose synthesis inhibitors using live cell imaging of Cellulose Synthase (CESA) in Physcomitrella patens - Mai L. Tran (Nature Portfolio, 2018)
Abstract Results from live cell imaging of fluorescently tagged Cellulose Synthase (CESA) proteins in Cellulose Synthesis Complexes (CSCs) have enhanced our understanding of cellulose biosynthesis, including the mechanisms of action of cellulose synthesis inhibitors. However, this method has been applied only in Arabidopsis thaliana and Brachypodium distachyon thus far. Results from freeze fracture electron microscopy of protonemal filaments of the moss Funaria hygrometrica indicate that a cellulose synthesis inhibitor, 2,6-dichlorobenzonitrile (DCB), fragments CSCs and clears them from the plasma membrane. This differs from Arabidopsis, in which DCB causes CSC accumulation in the plasma membrane and a different cellulose synthesis inhibitor, isoxaben, clears CSCs from the plasma membrane. In this study, live cell imaging of the moss Physcomitrella patens indicated that DCB and isoxaben have little effect on protonemal growth rates, and that only DCB causes tip rupture. Live cell imaging of mEGFP-PpCESA5 and mEGFP-PpCESA8 showed that DCB and isoxaben substantially reduced CSC movement, but had no measureable effect on CSC density in the plasma membrane. These results suggest that DCB and isoxaben have similar effects on CSC movement in P. patens and Arabidopsis, but have different effects on CSC intracellular trafficking, cell growth and cell integrity in these divergent plant lineages.